Pengembangan Perikanan Lobster di Provinsi Lampung - Siti Hudaidah; Yudha Adiputra; Margie Brite; Andhika Bayu Saputra; Dede Nur Abdul Halim; Firmansyah User (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
Spiny lobster fisheries in Lampung Province Indonesia has been developed since 1980. Local fisherman catched and sold spiny lobsters to local dealers before marketed to consumers. Only limited studies has been recorded about spiny lobsters fisheries, in particular for biology and social-economics aspects those may support spiny lobster development in the future. This study conducted in August until December 2016 with indepth survey to several local lobsters fisherman and dealer. This study showed, spiny lobster fisheries not developed rapidly. More over, decreased volume with limited valuable species and small size spiny lobster found in catch season. It is need to develop lobster fisheries not only limited to catched but also aquaculture.Spiny lobsters also need to develop to advances knowledge to support increasing demand and conserve their resources with stocks enhancing within lobsters biology relevances. Road maps were develop for short and long terms research as a guidelines for public to follow in particular for reproductive physiology. This paper also discuss about not allowing for puerulus and egg berried female catch and sold regulations and their effect to spiny lobster fisherman.